Strategies for Addressing Non-Communicable Diseases: A Global Health Policy Analysis Based on WHO Publications - Fazsya Tatra Khalia (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
Non-communicable diseases remain the leading cause of global mortality, yet policy responses vary significantly across countries, raising questions about how international health governance frameworks shape national strategies. This study examines how the World Health Organization conceptualizes and operationalizes NCD prevention through its normative publications, using a non-empirical qualitative policy analysis based on a structured review of WHO reports, action plans, and implementation frameworks published over the past fifteen years. Thematic coding and cross-document comparison were employed to identify dominant policy framings, implementation logics, and governance narratives embedded in these texts. The analysis finds that WHO strategies consistently prioritize structural prevention, institutional integration, and economic justification, framing chronic disease control as a development and governance issue rather than solely a biomedical one. Implementation guidance emphasizes adaptive diffusion, cost-effective interventions, and monitoring systems designed to institutionalize preventive policy. The study concludes that WHO publications operate as normative governance tools shaping how states define responsibility, allocate resources, and legitimize health interventions. These findings contribute to global health policy scholarship by demonstrating how international policy texts influence domestic reform trajectories through framing, institutional logic, and political economy narratives.